Exploring the outcomes of group reflective learning for school leaders. Issue 5 (2nd September 2020) - Daniëls, Ellen; Hondeghem, Annie; Heystek, Jan
ABSTRACT: Research on school leaders' professional development is scarce. Knowledge about school leaders' professional development is important with regard to keeping the position of school leaders attractive and pupils' achievement. The current article explores the outcomes of a group reflective learning programme for school leaders. The programme focused on one of the school leaders' prioritised professional development needs: coaching teachers. Nineteen school leaders participated in the programme and were interviewed after the programme. The interviews gauged school leaders' perceptions of learning outcomes and impact on their professional behaviour. The transcriptions of the interviews were analysed using a coding tree. The school leaders indicated that they gained theoretical knowledge, that they developed their coaching skills and their way of providing feedback. The school leaders stated that they valued group reflective learning because they learned to approach situations from various angles. Moreover, the school leaders reported increased levels of self-confidence and no longer feeling responsible for solving all problems by themselves.